2016 IEEE International Conference on Dielectrics (ICD) 2016
DOI: 10.1109/icd.2016.7547553
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resin/hardener stoichiometry on the electrical properties of silicon nitride/epoxy nanocomposites

Abstract: Abstract-The effect of resin/hardener stoichiometry was investigated for both unfilled epoxy and nanocomposite samples. The results indicate that incorporating silicon nitride nanofiller, which contains amine groups on its surface, has a significant influence on the resin/hardener reaction. At 2 wt.% of nanofiller, it was estimated that the powder contains amine groups equivalent to around 5 wt.% of the hardener mass, which results in the displacement of the optimum resin/hardener mass ratio by the same amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The surface chemistry of the silicon nitride is characterized by the existence of amine and hydroxyl groups (oxynitride surface chemistry) [44,45]. Previous work has shown that the amine hydrogens can chemically react with the epoxy groups in the resin [46,47]. On one hand, this has the advantage of making silicon nitride inherently compatible with the matrix polymer, which should result in good particle dispersion and, thus, minimize the effect of particle agglomeration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface chemistry of the silicon nitride is characterized by the existence of amine and hydroxyl groups (oxynitride surface chemistry) [44,45]. Previous work has shown that the amine hydrogens can chemically react with the epoxy groups in the resin [46,47]. On one hand, this has the advantage of making silicon nitride inherently compatible with the matrix polymer, which should result in good particle dispersion and, thus, minimize the effect of particle agglomeration.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarizes the prepared samples along with relevant details; the procedures used to prepare these samples are detailed elsewhere [46,47] and, consequently, are not repeated here, for the sake of brevity. All samples were stored under vacuum for at least two weeks prior to examination [54], in order to ensure that they were dry before any data were acquired.…”
Section: Nanocomposite Preparationmentioning
confidence: 99%
“…These properties are highly sensitive to the presence of dielectric e.g. metallic nano-particles with high microwave absorption properties [106][107][108][109], and can also be affected by sample preparation [49,56,[110][111][112][113][114][115], moisture [116][117][118], and temperature [119,120]. There has also been a slight confusion of using different terms as 'dielectric constant' in different literatures.…”
Section: Dielectric Properties Of Compositesmentioning
confidence: 99%
“…Indeed, an investigation by Nguyen et al [12] of epoxy resins demonstrated the marked reduction in dielectric breakdown strength that occurs when systems are formulated using an unbalanced stoichiometry. Separate work has demonstrated that the presence of unreacted amines can markedly increase electrical conductivity [13]. Although such results cannot demonstrate unambiguously that residual functional groups degrade the electrical properties of cured epoxy resins, they do highlight stoichiometry as a relevant and contributory factor.…”
Section: Introductionmentioning
confidence: 95%